2019
DOI: 10.1073/pnas.1819398116
|View full text |Cite
|
Sign up to set email alerts
|

Laminar segregation of sensory coding and behavioral readout in macaque V4

Abstract: Neurons in sensory areas of the neocortex are known to represent information both about sensory stimuli and behavioral state, but how these 2 disparate signals are integrated across cortical layers is poorly understood. To study this issue, we measured the coding of visual stimulus orientation and of behavioral state by neurons within superficial and deep layers of area V4 in monkeys while they covertly attended or prepared eye movements to visual stimuli. We show that whereas single neurons and neuronal popul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 41 publications
11
40
0
Order By: Relevance
“…Spiking activity was recorded with 16-channel linear array microelectrodes ( Fig. 1a) arranged so that receptive fields (RFs) on all channels largely overlapped 22,26 . During recordings, monkeys performed a spatial attention task, which required detecting changes in the orientation of a visual stimulus in the presence of distractor stimuli.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Spiking activity was recorded with 16-channel linear array microelectrodes ( Fig. 1a) arranged so that receptive fields (RFs) on all channels largely overlapped 22,26 . During recordings, monkeys performed a spatial attention task, which required detecting changes in the orientation of a visual stimulus in the presence of distractor stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…1). In each session, data from each of the recording channels were assigned laminar depth, relative to a common current source density marker 26 . We found that noise correlations were slightly reduced in superficial and enhanced in deep layers in the attention relative to control conditions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies have found evidence that subpopulations of neurons within visual cortex may be engaged differently during attention (Mitchell, Sundberg, & Reynolds, 2007;Nandy, Nassi, & Reynolds, 2017;Pettine, Steinmetz, & Moore, 2019) and working memory (van Kerkoerle et al, 2017). Thus, we next asked if the rule signals we observed might be driven disproportionately by distinct subsets of neurons recorded in the daily sessions.…”
Section: P=005)mentioning
confidence: 85%
“…Lastly, we found that neurons with robust task rule signals were distributed equally across layers of V4. Previous studies have shown that both attention and working memory influence neuronal activity differently across layers of visual cortex, including in V4 (Nandy et al, 2017;Pettine et al, 2019;van Kerkoerle et al, 2017). Since our array recordings were made largely perpendicular to the cortical surface (Fig.…”
Section: P=005)mentioning
confidence: 99%